Cell-free fetal DNA in amniotic fluid supernatant for prenatal diagnosis - Soltani, M; Nemati, M; Maralani, M; Estiar, M A; Andalib, S; Fardiazar, Z; Sakhinia, E (Cellular and Molecular Biology, 2016)
In widespread conviction, amniotic fluid is utilized for prenatal diagnosis. Amniotic fluid supernatant is usually discarded, notwithstanding being a good source of fetal DNA. The aim of the present study was to assess cell-free fetal DNA extracted from amniotic fluid supernatant for application in prenatal diagnosis such as gender determination and early diagnosis of Î²-thalassemia. Samples of amniotic fluid of 70 pregnant women were collected and went through routine tests along with tests for cell-free fetal DNA from amniotic fluid supernatant. The DNA in the amniotic fluid supernatant was extracted and analyzed for gender determination by PCR and Real-time PCR. ARMS-PCR was applied to test early diagnosis of IVS II-I mutation (common Î²-thalassemia mutation) and E7V mutation for sickle cell anemia using DNA extracted from the amniotic fluid supernatant. Using the cell-free fetal DNA extracted from the amniotic fluid supernatant, the sensitivity of PCR and Real-time PCR for gender detection was compared with the routine cytogenetic method. The fetus tested for sickle cell anemia and Î²-thalassemia was observed to be healthy but heterozygous for IVS II-I mutation. The findings indicated that cell-free fetal DNA from amniotic fluid supernatant can be a good source of fetal DNA and be used in early prenatal diagnosis since because of its fast and accurate application. Therefore, it would be suggested that the amniotic fluid supernatant's disposal is prevented because if the tests needs to be repeated, cell-free fetal DNA extracted from the amniotic fluid supernatant can be used as an alternative source for prenatal diagnosis.